Current Issues of the Authority and Effectiveness of EU/EEA Law? State Liability for Judicial Breaches and the Right to Retrial - Atli Lilliendahl 1995- (2021)
This thesis explores the issue of authority and effectiveness of EU and EEA law in connection with the potential application of the principle of State liability for judicial breaches in EEA law and the possibility of a retrial or a reopening of an EEA relevant case, having the status of res judicata, in Iceland. In EU and EEA academia, there have been extensive studies on the principle of State liability and the extension of the principle to covering breaches of the judiciary in the EU, while the principle is still pending confirmation in the EEA. Moreover, in EU law centred literature, the possibility of a retrial or a reopening has been somewhat researched, albeit not as methodically. However, as EU and EEA law are dynamic fields of law, therefore it is time for an update in the research literature, especially since the Icelandic State established, in December 2020, a new specialized Court for the Reopening of Judicial Cases to, inter alia, meet its EEA obligations. As this Court was established so recently, there is no literature yet, covering its establishment and what effects the new Court will have on the EEA rights of individuals and legal operators in Iceland. To address this issue and current research gap, this thesis examines the relevant literature, and explores if there has been an update in the case law of the CJEU or the EFTA Court. Moreover, this research is comparative and empirical, as by comparing and observing the trends in the EU law literature and CJEU case-law, one can make an educated guess what the future legal situation in EEA law entails. The outcome of the research is an implication that the Icelandic state, is possibly not fulling its full EEA obligations, with the establishment of the new Court of Reopening of Judicial Cases, as an analysis of the relevant legislation shows, that the new Court, might not be equipped well enough to react to all issues relating to the authority and effectiveness of EEA law.